Age Specific Optimal Allocation of COVID-19 vaccine supply in India - Talati, Isha; Shah, Devanshi; Shaikh, Azharuddin; Patel, Amisha; Mishra, Poonam (Journal of Applied Nonlinear Dynamics, 2026)
India is the second most populated country in the world and supply of COVID-19 vaccine is limited. Thus the effective use of COVID-19 vaccine is important. Here we have formulated an age structure SIRS model (Susceptible-infected-recovered- of COVID-19 in India. This model helps us to understand the characteristics of COVID-19 in with and without vaccination scenario. To formulate this model we have considered population factors like contact structure and country specific age structure. Further using optimization algorithm (GA) paired with age stratified mathematical model; we have determined optimal allocation for three matrices-infections, year of life loss, death.We have found that a vaccine with efficacy $≥ 70%$ would be enough to control death, infection and year of life loss.